Schema activation and working memory: the effect of different prereading activities on pre-intermediate and advanced Brazilian EFL students? reading comprehension - Rondon, Tatiana Koerich (2019)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2019.